HAMEMAYU HAYUNING BAWANA AS CULTURAL CAPITAL IN THE POST-TRAUMATIC RECOVERY AND GROWTH OF SEXTORTION VICTIMS IN INDONESIA - Prasanda, Maharani Jiny; Madani, Cikal; Nisa, Nabilatun; Qoni’ah, Siti; Dharmaputra, Haikal Erlangga; Mahfud, Ashari (Program Studi Bimbingan dan Konseling Universitas Tunas Pembangunan Surakarta, 2025)
This study explores the integration of Hamemayu Hayuning Bawana (HHB) a Javanese philosophical value emphasizing moral refinement and harmony with the universe as a cultural framework for post-traumatic recovery among sextortion survivors in Indonesia. Using a mixed-method explanatory research design, the study involved 137 participants who completed the Impact of Event Scale-Revised (IES-R), followed by in-depth interviews with three female survivors and two Javanese cultural experts. Quantitative data revealed high levels of post-traumatic distress, particularly in the dimension of avoidance, while qualitative findings illustrated seven stages of recovery aligned with the Post-Traumatic Growth (PTG) model. Survivors demonstrated psychological adaptation through processes of self-reflection, social support, emotional regulation, and spiritual renewal. The integration of HHB values Mangasah Mingising Budi (moral and cognitive refinement) and Memasuh Malaning Bumi (restoring balance and cleansing negativity) facilitated the development of new meaning, resilience, and self-acceptance. The study proposes a culturally grounded self-help model for trauma recovery that bridges indigenous philosophy and psychological theory, offering implications for culturally responsive counseling practices in Indonesia.